Meningkatkan Pemahaman Tentang Larangan Perundungan Melalui Media Ular Tangga: Perspektif Agama Islam Pada Siswa Kelas IV SDN 036 Ujung Berung - Anggi Rostiani Nurjanah; Dian Salsabila; Isabella Putri Shufania; Nadya Zulfi Soleha; Siti Hardianti Fitri; Asep Rudi Nurjaman (Universitas Muhammadiyah Bandung, 2024)
In the view of the Islamic religion, bullying is an action that is inappropriate for every community to carry out because it has a negative impact on life. However, in reality, people still carry out these actions even though this prohibition has been explained in the Islamic religion. Bullying that is often encountered includes physical bullying, verbal bullying, relational bullying, and cyber bullying. Bullying in any form has a negative impact on both the victim and the perpetrator, the victim can experience mental problems such as anxiety disorders while the perpetrator can also experience emotional disorders. Therefore, this research was carried out to develop learning media in the form of